European guideline (EuroGuiDerm) on atopic eczema – part II: non‐systemic treatments and treatment recommendations for special AE patient populations. (3rd September 2022) - Wollenberg, A.; Kinberger, M.; Arents, B.; Aszodi, N.; Avila Valle, G.; Barbarot, S.; Bieber, T.; Brough, H.A.; Calzavara Pinton, P.; Christen‐Zäch, S.; Deleuran, M.; Dittmann, M.; et al.
Abstract: The evidence‐ and consensus‐based guideline on atopic eczema was developed in accordance with the EuroGuiDerm Guideline and Consensus Statement Development Manual. Four consensus conferences were held between December 2020 and July 2021. Twenty‐nine experts (including clinicians and patient representatives) from 12 European countries participated. This second part of the guideline includes recommendations and detailed information on basic therapy with emollients and moisturizers, topical anti‐inflammatory treatment, antimicrobial and antipruritic treatment and UV phototherapy. Furthermore, this part of the guideline covers techniques for avoiding provocation factors, as well as dietary interventions, immunotherapy, complementary medicine and educational interventions for patients with atopic eczema and deals with occupational and psychodermatological aspects of the disease. It also contains guidance on treatment for paediatric and adolescent patients and pregnant or breastfeeding women, as well as considerations for patients who want to have a child. A chapter on the patient perspective is also provided. The first part of the guideline, published separately, contains recommendations and guidance on systemic treatment with conventional immunosuppressive drugs, biologics and janus kinase (JAK) inhibitors, as well as information on the scope and purpose of the guideline, and a section on guideline methodology.